Early life administration of Bifidobacterium bifidum BD-1 alleviates long-term colitis by remodeling the gut microbiota and promoting intestinal barrier development - Peng, Chenrui; Li, Jinxing; Miao, Zhonghua; Wang, Yunyi; Wu, Simou; Wang, Yimei; Wang, Silu; Cheng, Ruyue; He, Fang; Shen, Xi (Frontiers in Microbiology, 2022)
Inflammatory bowel disease (IBD) is a chronic intestinal disease characterized by microbiota disturbance and intestinal mucosal damage. The current study aimed to investigate the preventive effects of Bifidobacterium bifidum BD-1 (BD-1) against long-term IBD and possible mechanism by which it alters the gut microbiota, immune response, and mucosal barrier. Our study found that early treatment of BD-1 + Ceftri (ceftriaxone followed by BD-1) and BD-1 confers a certain protective effect against the occurrence of long-term Dextran sulfate sodium -induced colitis, which manifests as a decrease in inflammation scores and MPO activity levels, as well as a relatively intact intestinal epithelial structure. Moreover, compared to BD-1, Ceftri, and NS, early treatment with BD-1 + Ceftri promoted greater expression levels of mucosal barrier-related proteins (KI67, MUC2, ZO-1, slgA, Clauding-1, and Occludin), better local immune responses activation, and moderately better modulation of systemic immune responses during long-term colitis. This may be due to the fact that BD-1 + Ceftri can deliberately prolong the colonization time of some beneficial microbiota (e.g., Bifidobacterium) and reduce the relative abundance of inflammation-related microbiota (e.g., Escherichia/Shigella and Ruminococcus). Interestingly, we found that the changes in the gut barrier and immunity were already present immediately after early intervention with BD-1 + Ceftri, implying that early effects can persist with appropriate intervention. Furthermore, intervention with BD-1 alone in early life confers a certain anti-inflammatory effect in the long-term, which may be due to the interaction between BD-1 and the host’s native gut microbiota affecting intestinal metabolites. In conclusion, BD-1 was not as effective as BD-1 + Ceftri in early life, perhaps due to its failure to fully play the role of the strain itself under the influence of the host’s complex microbiota. Therefore, further research is needed to explore specific mechanisms for single strain and native microbiota or the combination between probiotics and antibiotics.